Single-Surgeon Experience for Maximizing Outcomes in Implant-Based Breast Reconstruction in Chinese Patients. Issue 3 (March 2019) - He, Shanshan; Yin, Jian; Sun, Jingyan; Huang, Qingfeng; Liu, Jing; Han, Chunyong; Yin, Zhuming
Abstract : Introduction: Breast reconstruction for Chinese patients is vastly different given cultural differences, patient preferences, access to resources, and insurance coverage in China. Given these unique factors, a different approach for optimizing outcomes should be considered. Methods: Retrospective review of all patients undergoing implant-based breast reconstruction from January 2013 to May 2016 was performed. Esthetic evaluations were made both by the patients and 1 nonoperative surgeon at least 6 months postoperative, and patient satisfaction was assessed using the Breast-Q. Results: Overall, 135 patients undergoing 141 implant-based breast reconstructions were reviewed. The majority of implants (n = 134) were placed in a subpectoral position, whereas 7 were placed prepectorally, and no acellular dermal matrix was used. Given the limitations in acellular dermal matrix usage, soft-tissue coverage was augmented with local regional flaps. Ninety-four reconstructions (66.7%) used latissimus dorsi, 39 (27.7%) used serratus anterior, and 7 (5.0%) used mastectomy skin flaps only for implant coverage. Four patients (2.8%) underwent revision surgery to the reconstructed breasts. Grade III and grade IV capsular contracture was observed in 10 (7.1%) and 2 (1.4%) reconstructions, respectively. Both the patient's and the surgeon's satisfaction were higher than 80% in breast symmetry. Conclusions: Our implant selection method fit the Chinese population characteristics and could be extended to different types of implant-based breast reconstruction. It produced good esthetic outcomes and was reproducible, predictable, and simple to master in the clinical setting. Abstract : Supplemental digital content is available in the text.